Fuzzy Delphi Method Application In The Development Of I-Tourism In Arabic For Specific Purpose - Mohammad Najib Jaffar; Azman Ab Rahman; Mohd Nizwan Musling; Nurkhamimi Zainuddin; Mohammad Imran Ahmad; Muhammad Sabri Sahrir (Ijaz Arabi Journal of Arabic Learning, 2022)
A study on the development of the i-Tourism smartphone application needs to be carried out to meet the needs of the Islamic and Shariah related tourism sector in Malaysia as well as enhancing the Arabic language as the learning medium and practical use in daily life. This study is conducted to examine the i-Tourism application, whose effectiveness is assessed by experts from the aspects of usability, ease of use, user satisfaction, and the technology of this application by using Fuzzy Delphi method (FDM) analysis. The research findings show that the experts rejected most of the items found in the four aspects, namely application usability, ease of use, user satisfaction, and application techniques. According to experts, the application developed is not too unique, and the information provided can still be accessed through a Google search. Some experts stated that the developed application seems to be still at an early stage because it does not have a lot of information and functions. As for the relation to learning and teaching Arabic, this mobile application is an output product based on research-based analysis which was enhanced and developed from theoretical aspects and phases of Arabic for specific purpose (ASP)